Smoking behavior and associated factors among the residents aged between 15 and 69 years in Fengxian District, Shanghai - HAN Wei; WANG Weibing; XU Hui; ZHANG Mingmin; YAN Zhaoxi; CHEN Ying; XIE Yang (Shanghai yufang yixue)
ObjectiveTo explore the relationship between smoking behavior and related factors among the adult residents in Fengxian District,so as to provide an evidence for carrying out tobacco control and other health promotion work.MethodsA multi-stage stratified cluster random sampling method was used to select 2 272 community residents aged between 15 and 69 yeas to carry out the questionnaire survey.ResultsIn 2020, the smoking rate of adult residents in Fengxian District was 23.50%. Smoking behavior was statistically correlated with age, gender, household registration, chronic disease, occupation and educational level. Smoking behavior was inversely correlated with educational level. Smoking rate of male residents was significantly higher than that of female residents, smoking rate of residents with chronic diseases was significantly higher than that of those without suffering from chronic diseases, and smoking rate of permanent registered residents was significantly higher than that of those non-locals. The highest smoking prevalence was among retired and freelancers, followed by staff of government agencies and public institutes, while the lowest was among students, followed by intellectuals. Multivariate logistic regression analysis showed that gender, age and education level were the main factors affecting the smoking prevalence level.ConclusionThe general smoking rate of adult residents in Fengxian District was higher than the average level in Shanghai but lower than the national level. Male residents aged ≥25 years and with lower education level are the key invention targets for tobacco control.